2011
DOI: 10.1007/s00421-011-1907-2
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte apoptosis and pro-/anti-apoptotic proteins following downhill running

Abstract: The purposes of this study were to determine the effect of eccentric exercise-induced muscle damage on the induction of apoptosis in peripheral blood leukocytes and to investigate if the elevation in apoptotic leukocytes was mediated by changes in the concentration of anti-/pro-apoptotic proteins in circulation. Twelve moderately trained subjects performed three 40 min treadmill runs at ~70% VO(2max): a level run (L) followed by two downhill runs (DH1 and DH2). Blood samples were taken at rest (PRE) and immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
16
1
4
Order By: Relevance
“…This velocity was maintained throughout each downhill running trial. This difference between flat and downhill running is similar to that found in previous literature (51).…”
Section: Participantssupporting
confidence: 91%
“…This velocity was maintained throughout each downhill running trial. This difference between flat and downhill running is similar to that found in previous literature (51).…”
Section: Participantssupporting
confidence: 91%
“…The aim of our study was to examine the effects of combined antioxidant supplementation on markers of muscle damage, DOMS, and antioxidant status after repeated downhill runs. Consistent with previous studies [12,27,30,[34][35][36], the repeated bout effect was evident in our study: CK activity and DOMS were significantly lower following 2D than 1D, and ORAC was up-regulated before 2D compared to 1D. The beneficial effect of eccentrically-biased exercise on health-related parameters and muscle performance has been shown by several researchers [32,33,37].…”
supporting
confidence: 92%
“…A power analysis based on previous literature [35,36] indicated that 11 subjects/group were required to detect a 52 % change in the CK activity (U/L) (the primary outcome variable) with 80 % power at α = 0.05. Data were analyzed using a mixed model ANOVA with repeated measures followed by adjusted Tukey post hoc tests using SAS (9.3).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Lymphocytes decrease rapidly to a level well below the pre-exercise value, whereas granulocytes can remain increased for several hours after exercise [3][4]. This decline in lymphocyte count may last from several hours up to days and may, at least in part, account for post-exercise immune suppression [5][6]. The majority of studies investigated the effects of exercise on lymphocyte apoptosis and proposed exercise intensity and duration as two determinants of lymphocyte apoptosis [7][8][9][10].…”
Section: Introduction *mentioning
confidence: 99%
“…Unaccustomed downhill running is known to induce more muscle damage compared to uphill or level runs [6,19,20]. A causative role for eccentric exercise-induced muscle damage is ascribed to the mechanical stress that occurs when muscles lengthen and generate break force upon foot strike to maintain balance against gravity [6,11]. Even though exercise-induced muscle damage is known to be associated with an increase in leukocyte apoptosis in peripheral blood,…”
Section: Introduction *mentioning
confidence: 99%